RISK FACTORS IMPACTING KID SURVIVAL OF BLACK BENGAL GOATS RAISED IN FIELD CONDITION OF WEST BENGAL, INDIA - Sanjoy Datta; Manoranjan Roy; Uttam Sarkar; Subhash Taraphder; Santanu Bera; Apratim Maity (Exploratory Animal and Medical Research)
Kid mortality due to various factors leads to substantial economic losses for goat farmers. This study assessed the survival rates of Black Bengal goat kids from birth to 12 months, analyzing data from 11,996 kids raised across different agro-climatic clusters in West Bengal, India, over the period 2010-2021. Birth weight, cluster, year and season of birth, type of birth, sex, and parity of kidding were considered as key variables. At birth, the survival rate was recorded at 99.86%, with 90.96% of kids surviving through the critical period of up to 3 months. The overall survival rate by 12 months was 85.55%. The significant factors influencing survival up to 3 months, identified through maximum-likelihood analysis of variance, included birth weight, cluster, season of birth, sex, and type of birth. Among the clusters, the Jalpaiguri cluster exhibited the highest survival rate up to 3 months (98.70%), followed by Jhargram (95.82%), Sundarban (93.47%), Murshidabad (87.03%), and Nadia (86.95%). These variations were linked to differences in agroclimatic conditions, availability of grazing pastures, and environmental factors. Kids born during summer showed a higher survival rate (92.14%) compared to those born in other seasons. Furthermore, kids with a birth weight exceeding 1.5 kg exhibited the highest survival rate (86.28%) up to 12 months. The findings highlight the potential to improve goat productivity by adopting enhanced management practices and prioritizing the selection of larger kids at birth.